Livestock development and climate change in Turkana District, Kenya - Notenbaert, An Maria Omer; Thornton, Philip K.; Herrero, Mario (International Livestock Research Institute, 2007)
The main purpose of the study presented here is to shed some light using simple and aggregated methods on the following question: In view of the expected climate change, is there also a long-term perspective for livestock development in the area, i.e. will the Turkana ecosystem be able to sustain livestock production during the next few decades? In our search for an answer to this question, we looked at the current pressure on the environment, tried to interpolate the predicted climate change to the Turkana District scale and started exploring some of the possible impacts of climate change on the environment and the people depending on it. Due to the simplistic nature of the analyses performed, we consider these figures to be indicative only. This study goes hand in hand with another one focussing on market access and opportunities.